1989
DOI: 10.1016/0741-5214(89)90227-9
|View full text |Cite
|
Sign up to set email alerts
|

Results of supraceliac aortic clamping in the difficult elective resection of infrarenal abdominal aortic aneurysm

Abstract: We have used clamping of the aorta above the celiac axis (SC) in 30 of 431 elective resections of infrainguinal abdominal aortic aneurysms (AAA) during the past five years as an alternative to a difficult aortic cuff dissection. The results of SC clamping in these 30 patients are compared with the results of 379 routine aneurysm resections with infrarenal (IR) clamping and 22 additional aneurysm resections where the clamp was placed immediately above the renal arteries. These difficult cuff dissections occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
53
3
2

Year Published

1992
1992
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(59 citation statements)
references
References 14 publications
1
53
3
2
Order By: Relevance
“…With regard to the risk of renal morbidity, we documented high rates of transient renal insufficiency of up to 70% for the JRA group in our series. This is much higher than that reported in other large studies (20-41%) in the past [4,6,8,9,13,14,16,17]. We trace this back to our stringent definition of renal failure, which starts at a creatinine level of 1.3 mg/dl [1] in contrast to other studies (>1.8 mg/dl).…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…With regard to the risk of renal morbidity, we documented high rates of transient renal insufficiency of up to 70% for the JRA group in our series. This is much higher than that reported in other large studies (20-41%) in the past [4,6,8,9,13,14,16,17]. We trace this back to our stringent definition of renal failure, which starts at a creatinine level of 1.3 mg/dl [1] in contrast to other studies (>1.8 mg/dl).…”
Section: Discussionmentioning
confidence: 59%
“…A big issue with regard to the question of clamping location for JRA repair is also present in the literature. The study of Green et al [9] established that supravisceral clamping is safer than suprarenal clamping, due to the avoidance of embolization of atherosclerotic debris from the perirenal region. The San Francisco Group [13] and the Cleveland Clinic [17] already mentioned the methodological errors of Green's analysis on patients in whom complications developed due to failed infrarenal cross-clamping [9].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…4 Furthermore, Green et al 5 identified atheroemboli to be another cause of postoperative renal insufficiency due to a suprarenal aortic cross-clamp.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] Nypaver et al 19 reported that aortic control immediately proximal to the renal arteries may prove problematic because of pararenal aortic atherosclerosis or proximity of the superior mesenteric artery to the renal arteries; they advocated supraceliac aortic cross-clamping as a safe and valuable technique for achieving proximal control in complex abdominal aortic repair. In their series, when the supraceliac aortic cross-clamping time was limited to less than 30 min, postoperative vital organ ischemic complications such as renal, hepatic, mesenteric, or spinal cord injury were rare.…”
Section: Discussionmentioning
confidence: 98%